STUDI DAN EVALUASI KANDUNGAN LOGAM BERAT BESI (Fe) DAN MANGAN (Mn) PADA AIR DAN SEDIMEN DI PERAIRAN SUNGAI KOTA TARAKAN - Syahril .; Ratno Achyani (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2015)
The purpose of this study is to provide information regarding the content, concentrations and status of heavy metals Fe and Mg on water and sediment in the waters of the Tarakan City. Materials used are samples of water and sediment samples. Analysis of heavy metals in water and sediment using Kausik (2009). the results analysis is showed the presence of heavy metals Fe and Mn in water and sediment. Fe concentration on water samples ranged 0,145-0,220 mg/L. The highest area was the River Strat Buntu 0,220 mg/L and the lowest area are Juata KORPRI 0,145 mg/L. Mg concentration on water samples ranged 4,290-0,422 mg/L. The highest was river KKMB 4,290 mgl/l and the lowest at Juata Laut 0,422 mg/L. Heavy metal Fe concentration on sediment was ranged 0,177-1.751 mg/L. The highest was on KKMB 1,751 mg/l and the lowest was Juata Sea 0,177 mg/L. Heavy metal Mg concentration on sediment samples was ranged 0,457-3.721 mg/L. Mg supreme concentration was KKMB 3,721 mg/L and the lowest at Juata Laut 0,457 mg/L. Status of heavy metal concentrations in waters are generally above the threshold quality standards required and on sediments is still below the threshold quality standards required. Keywords : heavy Metals, sediments, waters, status, Tarakan City river